The Role of Autophagy in Pancreatic Cancer: From Bench to the Dark Bedside - Kıvanç Görgülü; Kalliope N. Diakopoulos; Ezgi Kaya-Aksoy; Katrin J. Ciecielski; Jiaoyu Ai; Marina Lesina; Hana Algül (Cells, 2020)
Pancreatic cancer is one of the deadliest cancer types urgently requiring effective therapeutic strategies. Autophagy occurs in several compartments of pancreatic cancer tissue including cancer cells, cancer associated fibroblasts, and immune cells where it can be subjected to a multitude of stimulatory and inhibitory signals fine-tuning its activity. Therefore, the effects of autophagy on pancreatic carcinogenesis and progression differ in a stage and context dependent manner. In the initiation stage autophagy hinders development of preneoplastic lesions; in the progression stage however, autophagy promotes tumor growth. This double-edged action of autophagy makes it a hard therapeutic target. Indeed, autophagy inhibitors have not yet shown survival improvements in clinical trials, indicating a need for better evaluation of existing results and smarter targeting techniques. Clearly, the role of autophagy in pancreatic cancer is complex and many aspects have to be considered when moving from the bench to the bedside.